Extraction of People’s Perception Toward Horseshoe Crab Existence in Northeast Coast of India - Pati, Siddhartha; Shahimi, Salwa; Edinur, Hisham Atan; Nelson, Bryan Raveen; Acharya, Diptikanta; Dash, Bisnu Prasad (Frontiers in Marine Science, 2020)
Understanding local community attitudes toward wildlife and environment is critical for making context-sensitive conservation planning and management decisions while facilitating better human–wildlife coexistence among Indian coastline communities. We conducted questionnaire-based interviews with 388 local households from12 different villages in Balasore, Odisha between September 2018 and February 2019. A theoretical framework was constructed by categorizing variables to explain attitudes and par them with key factors to derive local attitudes toward horseshoe crabs. We found that 53% of respondents were comfortable with horseshoe crab presence in their area, 27% were uncomfortable and the remaining 20% were having mixed-feelings. Respondents favored horseshoe crabs with tangible benefits such as aesthetic, monetary and cultural significance. Respondents with oppressive attitudes relate horseshoe crabs with fishing net damage. Both, principle component and step-wise analyses revealed that age, gender, and education were suitable indicators for local community perceptions with horseshoe crabs. We encourage socioeconomic monitoring particularly during rapid economic and infrastructure development to minimize knowledge erosion and to cherish local ecological knowledge for better production of scientific explorations concerning human-wildlife co-existence in India.